PENGARUH HAMBATAN SAMPING TERHADAP KINERJA RUAS JALAN SATU ARAH DAN DUA ARAH TANPA MEDIAN DI KOTAMADYA MATARAM - HASYIM HASYIM; ROHANI ROHANI (Universitas Mahasaraswati K. Mataram, 2023)
Street Catur Warga and Dr. Wahidin did not have enough stops, so many vehicles stopped on the shoulder of the road and parked on the side of the road. The number of people crossing the road and the number of vehicles entering/exiting the road causes a reduction in the speed, volume and capacity of the road so that at certain hours traffic jams often occur. This study analyzed the side friction, volume and speed of Catur Warga and Jalan Dr. Wahidin used the 1997 MKJI method. The results of the analysis on one-way roads, especially the Catur Warga road, had side friction, volume and speed respectively, namely 790.7 events/hour, 1533.75 smp/am and 46.08 km/hour. While the two-way street, Jalan Dr. Wahidin, has side friction, volume and speed of 403.1 events/hour, 1916.15 smp/hour and 38.58 km/hour. From the results of the regression analysis, side friction is very influential on the volume and speed of traffic. This can be seen from (r) in the range of 0.7 < r < 0.9 where the number shows a strong influence and 0.9 < r < 1 indicates a very strong influence. The results of partial regression analysis show that on the Catur Warga road, the side barriers that have the most influence on volume are Parking and Vehicle Stops (PSV), while at speed, namely Vehicles Exiting/Entering Roadside Land Use (EEV). On the Dr. Wahidin the side friction variable that has the most influence on volume is Pedestrians (PED), while at speed, namely Parking and Vehicle Stops (PSV).